Kemajemukan dalam Politik Etnis Masyarakat Urban: Studi pada Masyarakat Multi Etnik dan Agama di Kota Metro - Firmansyah, Firmansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
Politics has exertion to set accepted rules for the citizens to apply a harmonious life. This field study investigated the characteristics of sociopolitical of immigrants societies in Metro City which tend to groups based on their emotional feelings. It occurs because of their similarity. However, their synthesis and interaction in the social environment surprisingly go well. Sadly, their unity awareness can not compete and take over the parliamentary chair. The pluralism ethnic in Metro City is high, the core political power is dominated by indigenous societies. The presence of immigrant and indigenous societies in politic showed an effort to compete and promote Metro City in various aspects of life.